REVIEWS - Morgenstern, Matthew (Journal of Semitic studies, 2003)
A Grammar of Egyptian Aramaic (Handbuch der Orientalistik I:32) T.Muraoka and B.Porten . Brill, Leiden , 1998. Pp. xlix + 393. Price: €11118.00 hardback . ISBN: 90-04-10499-2.